Qualitative Exploration of Factors That Influence Snack Food Consumption During Infancy (P11-087-19). (13th June 2019) - Moore, Amy; Vadiveloo, Maya; McCurdy, Karen; Tovar, Alison
Abstract: Objectives: Less healthy snack food consumption has increased in young children, yet little is known about snack food consumption during infancy. This qualitative study explored how low-income mothers define snacking and factors that influence snack food consumption during infancy. Methods: A purposive sample of low-income mother-infant dyads ( N = 8) were recruited from Women, Infants, and Children (WIC) and childcare centers in Rhode Island. Semi-structured qualitative interviews were conducted when infants were approximately 6-months of age to explore the mother's definition of snacking and factors that influence when and what snack foods are offered to infants. Interviews were audio recorded, verbatim transcribed, and a thematic analysis was conducted. Results: Mothers were on average 27.3 years old (SD = 4.9), 62.5% identified as White, 25.0% as Multiracial, and 12.5% as African-American/Black. Mothers defined snacking as small feedings that help infants feel full between milk-feedings and exposes them to a variety of new flavors. Most mothers (75%) reported that they had offered snack foods to their infant by around 5 months of age, and 25% reported that they had decided not to offer snack foods due to concerns about choking (n = 1) and healthfulness (n = 1). Despite reporting that snack foods offered to infants should be healthy, most mothers (75%) expressed concerns about offering vegetables and fruits due to choking and reported offering snack foods that easily dissolve in the infant's mouth (e.g., puff and melts). Conclusions: Preliminary results suggest that mothers believed snack foods were an important part of infant feeding to ensure adequate caloric intake, exposure to new flavors, and a healthful diet while reducing choking risk. Given that many mothers will introduce snacks during infancy, it is critical to promote developmentally appropriate, healthy snacks. Future studies should explore other environmental factors that influence snack food consumption during infancy. Funding Sources: This work was supported by the USDA National Institute of Food and Agriculture, [Hatch/Tovar/1001894].